Pengembangan Media Pembelajaran Powerpoint pada Matepelajaran Matematika dengan Materi Bangun Datar untuk Siswa Kelas IV Sekolah Dasar - Saputri, Aprinda Ageng; Ain, Siti Quratul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The world's IT sector is no exception with Indonesia experiencing rapid development despite the Covid 19 pandemic, where the world of education is required to use and utilize a technology called computers. The study held below has a goal of developing media or materials used in the implementation of mathematics learning activities, especially in learning flat shapes using animation on the Microsoft Point application which is applied to grade IV (six) elementary school (SD) students. The purpose of this research is to examine the truth and readiness of the media or tools used in the implementation of mathematics learning activities, especially in learning to build flat using animations contained in the Microsoft PowerPoint application. The method used in this study is a quantitative method with a Research & Development (R&D) approach. This technique focuses on developing ADDIE through several stages, including (1) Analysis, (2) Designing, and (3) Development. Then 6 experts will test the validity, where this test will be divided into testing on design, language testing, and material testing, each of which requires at least 2 experts in their fields. The tool used in this study is the expert validation sheet. The results of this study are in the form of videos containing mathematics learning, especially in the fourth (sixth) grade flat shape learning. The animations contained in the Microsoft PowerPoint application were developed in the form of learning videos. The conclusion in the study of developing the media or tools used in this mathematics learning activity is in the